Zoothentic evaluation of tilapian alevines feed fed with kefir (Research, Society and Development, 2021)
Introduction: Probiotics have variable microbiological composition, which results in distinct by-product profiles and consequent beneficial probiotic action for animals. Objective: it aimed to characterize the microorganisms present in kefir samples and those stabilized in commercial rations for consumption in fish farming and to evaluate the result in a zootechnical profile. Methodology: The microbial quantification process of kefir grown in milk, brown sugar and feed mixed with grains and fermented solutions was carried out by decimal dilutions, plated in De Man Rogosa and Sharpe (MRS) medium for Lactobacillus, "Brain Heart Infusion", (BHI) for global bacterial count, glucose Sabouraud for yeasts and the NMP technique for coliforms at 35ºC and 45ºC and EMB for Escherichia coli. For the identification of the genus and species, mass spectrometry (Mald Tof) was used. Treatments with milk, grains and water with brown sugar were used, with kefir in the dose of 4% of the different forms for each kilogram of feed. Results: These treatments indicate changes in the results that are statistically significant in relation to the total size, partial size and width. As for weight, it showed statistically significant results only after 15 days of treatment. Conclusion: The experimental conditions used and the proportion of 4% of the feed did not influence the parameters of the zootechnical profile of the animals.